A mountain worth climbing: reforming the UN Department of Economic and Social Affairs - Heiner Janus; Silke Weinlich (Deutsches Institut für Entwicklungspolitik (DIE), 2018)
The United Nations Department of Economic and Social Affairs (UN DESA) is a key multilateral organisation for development. Since 2015, DESA has had the unique mandate of facilitating the efforts of all UN member states towards achieving the 2030 Agenda for Sustainable Development by supporting the High-level Political Forum. It is tasked to provide intellectual leadership through research and analysis, support norm-setting by the main UN bodies on development – the General Assembly (GA), the Economic and Social Council (ECOSOC) – and coord¬inate with the broader UN development system. However, DESA has yet to unlock its full potential in playing a politically relevant and analytically authoritative role in sustainable development beyond the conference rooms of New York. DESA's organisational structures have become increasingly outdated and inefficient. Since the founding of DESA in 1997, the department has been curiously exempt from the ongoing reforms of the world organisation. In addition, there is little transparency and analysis of actual reform needs and options. Our reform vision is that DESA should become a more prominent voice of the UN in sustainable development and help to credibly raise ambitions for the implementation of the 2030 Agenda globally. Tasked with economic and social affairs, DESA could serve as the multilateral hub for advancing universality, assisting all countries (including high-income countries) in striving for sustainable devel¬op¬ment and coordinating global policies towards advancing the global common good. This vision calls for a department that is intellectually brilliant, politically capable and impartial in bringing together the whole UN system. As a basic condition, DESA reform requires vigorous and consistent support from member states. The power of the Secretary-General (SG) and his heads of department to reorganise the structures are limited by member states' oversight, which is mainly executed in the UN's budgetary bodies. Moreover, DESA's substructures have expanded organically around mandated tasks, creating a highly decentralised entity with various overlapping activities, thereby raising the stakes of reform. The most recent reform attempts of DESA have stag¬nated in a geopolitical climate of mistrust and opposing priorities along the divisions between countries from the political North and South. DESA has been the home base of developing countries – organised as the Group of 77 and China (G77) – at the UN Secretariat, making it an advocate of developing-country interests. Since 2015, several countries from the political North (e.g. United States and EU countries) have called for DESA reform in terms of increasing effectiveness and efficiency, while the G77 has pushed back, suspecting attempts to diminish their power by cutting funding and staff. The situation has become increasingly complex, with growing speculation on the intentions of China, whose diplomats have been leading the department for the last decade. In order to prepare the ground for a comprehensive DESA reform that is beneficial to all stakeholders, we suggest three steps to the SG and his reform team that build upon each other: create greater transparency, substantive knowledge and participation on DESA reform interlink DESA reform with ongoing UN reform processes generate political support from member states and long-term payoffs from DESA reform.
Keywords: 330; Agenda 2030; Deutsche + Europäische + multilaterale Entwicklungspolitik